Katavi : Africa's fallen paradise [videorecording (DVD)] - Prümm, Owen; March, Nimmy; Prümm, Owen (PBS, 2025)
In the heart of Africa's Great Rift Valley lies Katavi, a little-known National Park spanning more than 3,000 square miles of western Tanzania. Here lions, hippos, and crocodiles live more or less in harmony, until an unusual climatic cycle transforms the natural dry season into the toughest drought in almost a century. Desperation pushes all the animals to the edge of their endurance. Lion cubs face mortal danger from a rogue male lion intent on a takeover. Hippos fight viciously for territory rights in a dwindling river. Even crocodiles, usually capable of surviving prolonged periods without food or fresh water, fall victim to the intense conditions. When the drought finally breaks, Katavi veers from one extreme to another. For some, the return of the rains brings not salvation, but further peril. As the planet heats, apocalyptic conditions could become more frequent.